Maternal Choline Intake Programs Hypothalamic Energy Regulatory Pathways and Long-Term Phenotype in Male Wistar Rat Offspring (OR35-04-19). (13th June 2019) - Hammoud, Rola; Pannia, Emanuela; Liao, Chih-Sheng; Chatterjee, Diptendu; Ho, Mandy; Yang, Neil; Kubant, Ruslan; Pausova, Zdenka; Anderson, G Harvey
Abstract: Objectives: The prenatal period is a critical time of brain development. Maternal choline intake is associated with improvement in memory and cognitive function in the offspring. However, the role of choline in the regulation of physiological functions controlled by the hypothalamus has not been reported. The objective of this study is to elucidate the effects of choline intake on the in utero programming of hypothalamic energy regulatory neurons in male Wistar rat offspring. Methods: Pregnant Wistar rats received an AIN-93G diet containing recommended choline (RC, 1 g/kg diet), low choline (LC, 0.5-fold), or high choline (HC, 2.5-fold). At birth, brain and blood was collected from male pups. Male pups from each dietary treatment were maintained on the control diet for 17-weeks. Dependent measures include post-weaning food intake, energy expenditure, weight-gain, plasma glucoregulatory hormones, brain choline and 1-carbon metabolite levels, and expression of hypothalamic energy regulatory neurons. Results: At birth, pup brain concentrations of choline proportionally reflected the choline content in the maternal diets. HC pups had higher hypothalamic protein expression of the orexigenic neuropeptide-Y neuron than both groups ( P < 0.05), but lower activation than LC pups ( P < 0.05). Both HC and LC pups had lower plasma leptin concentrations than RC pups ( P < 0.01), but LC pups had lower hypothalamic leptin receptor expression compared to both groups at birth ( P < 0.05). During adulthood, offspring of HC dams had higher weekly food intake compared to RC (11%, P < 0.01), and higher weight-gain than both RC and LC groups (12%, P < 0.05). LC offspring had lower 24hr energy expenditure and locomotor activity than HC and RC groups (6%, P < 0.05). Conclusions: Choline content of diets consumed by rats during pregnancy impacts in utero development of hypothalamic energy regulatory systems; long-term body weight-gain, food intake and energy expenditure in mature rat offspring. Funding Sources: This research was supported by the Canadian Institute of Health Research, Institute of Nutrition, Metabolism and Diabetes (CIHR-INMD).